IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA DI KELAS IV SD - Thera Dies Yunizha; Faizal Chan; Issaura Sherly Pamela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Culturally Responsive Teaching (CRT) approach in the teaching of Natural and Social Sciences (IPAS) on the topic "My Culturally Rich Indonesia" in Grade IV at SDN 55/I Sridadi, as well as to identify the supporting and inhibiting factors in its application. The CRT approach is used to create a contextual, inclusive, and meaningful learning process by integrating students’ cultural backgrounds into learning activities. This research uses a qualitative approach with a phenomenological method. Data were collected through observation, in-depth interviews, and documentation involving the classroom teacher, the principal, and fourth-grade students. The results of the study show that the teacher successfully designed and implemented culturally-based learning by connecting IPAS material with students’ local cultural experiences. Strategies used include the use of culturally-based learning media, the incorporation of folktales and regional songs, and engaging students in relevant cultural projects. Supporting factors in the implementation of CRT include the principal’s support, the flexibility of the Merdeka Curriculum, parental involvement, and the availability of local learning media. On the other hand, the challenges identified include limited instructional time, uneven student understanding of local culture, and the absence of specific teacher training on the CRT approach. Therefore, it can be concluded that the Culturally Responsive Teaching approach is effective in enhancing student engagement, understanding, and appreciation of Indonesia’s cultural diversity. This approach also strengthens students’ cultural identity and creates a learning environment that values diversity.